Peran Pondok Pesantren dalam Memberdayakan Kewirausahaan Santri di Pondok Pesantren Al-Risalah Batetangnga - Mutmainnah, Tiara; Sappeami; Rini, Rini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research is motivated by the still low involvement of students in entrepreneurial activities, the limited variety of business units, and the minimal marketing support and post-boarding school follow-up. The purpose of the research is to understand the role of Pondok Pesantren Al-Risalah Batetangnga in fostering the entrepreneurial spirit of the students. The research uses a qualitative approach with a case study method through interviews, observations, and documentation. Data analysis was conducted using the Miles & Huberman interactive model, and validity testing was performed using triangulation and member check. This research concludes that Al-Risalah Batetangnga Islamic Boarding School plays an important role in fostering the entrepreneurial spirit of its students through the formation of an independent mindset, practice-based training, the provision of business facilities such as cooperatives, and the instillation of Islamic values. This role not only equips students with technical skills but also shapes an entrepreneurial character that is independent, has integrity, and is responsible